MLSA phylogeny and antimicrobial susceptibility of clinical Nocardia isolates: a multicenter retrospective study in China - Wei, Ming; Xu, Xinmin; Yang, Jingxian; Wang, Peng; Liu, Yongzhe; Wang, Shuai; Yang, Chunxia; Gu, Li (BMC microbiology, 2021)
With the increase of detection rate and long treatment period, nocardiosis has become a noticeable problem in China. However, there are limited large-scale studies on the epidemiology and antimicrobial susceptibility profiles of clinical Nocardia spp. in China. The present study aimed to explore the species distribution and drug susceptibility pattern of 82 clinical Nocardia isolates from three tertiary hospitals in China by multilocus sequence analysis (MLSA) and broth microdilution (BMD) method. Pulmonary nocardiosis (90.2%) was the most common clinical presentation of infection. N. cyriacigeorgica (n = 33; 40.2%) and N. farcinica (n = 20; 24.4%) were the most frequently encountered Nocardia species, followed by N. otitidiscaviarum (n = 7; 8.5%), N. abscessus (n = 5; 6.1%), N. asiatica (n = 4; 4.9%), and N. wallacei (n = 4; 4.9%). Trimethoprim/sulfamethoxazole (SXT) remained high activity against all Nocardia isolates (susceptibility rate: 98.8%). Linezolid and amikacin were also highly active; 100 and 95.1% of all isolates demonstrated susceptibility, respectively. Except for N. otitidiscaviarum, all the Nocardia isolates exhibited high susceptibility rates to imipenem. The resistance rates of all isolates to clarithromycin and ciprofloxacin were 92.7 and 73.2%, respectively, but the resistance rate of N. farcinica to ciprofloxacin was only 25%. The clinically isolated Nocardia spp. had diverse antimicrobial susceptibility patterns, which were similar to the reports by other groups elsewhere, but some differences were also observed, mainly including imipenem and ciprofloxacin. According to this study, SXT still can be the first choice for empirical therapy due to the low resistance rate. Linezolid can be chosen when a patient is allergic to SXT, and amikacin and imipenem can be the choice in a combination regimen.